Ceramides affect alcohol consumption and depressive-like and anxiety-like behavior in a brain region- and ceramide species-specific way in male mice - Zoicas, Iulia; Huber, Sabine; Kalinichenko, Liubov; Gulbins, Erich; Müller, Christian P.; Kornhuber, Johannes (Addiction Biology, 2019)
Depression and alcohol dependence are associated with increased plasma ceramide concentrations in humans. Pharmacological increase in C16 ceramide concentrations in the dorsal hippocampus (DH) induced a depressive-like phenotype in naïve mice. However, the effects of C16 ceramide on alcohol consumption and anxiety-like behavior as well as the behavioral effects of other ceramide species are yet unknown. Therefore, we investigated whether repeated infusion of ceramides with different fatty acid chain lengths (C8, C16, and C20) into the DH and the basolateral amygdala (BLA) alter alcohol consumption, emotional behavior, and tissue monoamine levels. Our results revealed that C16, but not C8 and C20, ceramide altered alcohol drinking and emotional behavior in a brain region–specific way without altering tissue noradrenaline, dopamine, and serotonin levels in the prefrontal cortex, ventral striatum, and dorsal mesencephalon. In more detail, C16 ceramide increased alcohol consumption when infused into the BLA, but not when infused into the DH. Furthermore, C16 ceramide induced a depressive-like phenotype when infused into the DH, but a predominantly anxiogenic-like phenotype (in a non-social, but not a social context) when infused into the BLA. In turn, alcohol drinking normalized C16 ceramide-induced depressive-like and anxiogenic-like phenotypes. This study demonstrates a complex ceramide species-specific and brain region-specific modulation of alcohol consumption and emotional behavior in mice and provides the framework for future studies investigating the involvement of distinct ceramide species in the regulation of emotional behavior.
CRIS-Team Scopus Importer:2019-12-24
Keywords: alcohol consumption; basolateral amygdala; C16 ceramide; dorsal hippocampus; emotional behavior